2011
DOI: 10.1183/09031936.00188310
|View full text |Cite
|
Sign up to set email alerts
|

Rapid early weight gain is associated with wheeze and reduced lung function in childhood

Abstract: The aim of our study was to investigate the association between rapid weight gain in the first 3 months of life and the prevalence of wheeze in the first years of life and lung function at 5 yrs of age.The infants selected were participating in an ongoing birth cohort. Information on growth and respiratory symptoms was collected during the first year of life, and on primary care consultations during total follow-up. Forced expiratory volume in 1 s (FEV1) and forced expiratory flow at 25-75% of forced vital cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
(39 reference statements)
4
46
1
Order By: Relevance
“…Our findings are in contrast with those of other studies on the association between early life growth patterns and wheeze, which identified an association of weight growth [16][17][18][19][20] but no association of height growth [16][17][18][19] with later wheeze and/or asthma. In line with our findings, 2 other studies found no association between weight growth and later wheeze, 21,22 but no other study has reported an association of height growth and wheeze.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our findings are in contrast with those of other studies on the association between early life growth patterns and wheeze, which identified an association of weight growth [16][17][18][19][20] but no association of height growth [16][17][18][19] with later wheeze and/or asthma. In line with our findings, 2 other studies found no association between weight growth and later wheeze, 21,22 but no other study has reported an association of height growth and wheeze.…”
Section: Discussioncontrasting
confidence: 86%
“…18,22 Such conflicting results may derive from differences in methodological choices, such as definition of growth rates and timing of outcome measurements. In our study, growth was defined as difference scores of standardized weight, height, or BMI in 3 periods (age 1-7 months, age 7-14 months, and age 2-3 years), whereas others have categorized growth between age 0 and 2 years 21 or in several intermediate periods [16][17][18] into slow, normal, and rapid weight gain, or have used parameters of modeled growth curves to define growth patterns. 19,20,22 Sensitivity analyses with relative growth rates calculated over 1-3 months only as a determinant did not change our conclusions, however.…”
Section: Discussionmentioning
confidence: 99%
“…SONNENSCHEIN-VAN DER VOORT et al [127], DE KORTE-DE BOER et al [128], and PIKE et al [129] conducted cohort studies assessing the relationship between early growth (measured as weight and weight gain, height and height gain, and body mass index (BMI)) and later wheezing/asthma or lung function; others have also recently published their results [130]. The findings appear to be contradictory.…”
Section: Paediatric Respiratory Epidemiologymentioning
confidence: 99%
“…Investigators have reported a positive correlation of rapid infantile weight gain with wheeze at the age of 1, 3 and 4 years [1,3,10], with asthma up to the age of 10 years [4,11], with preschool asthma exacerbations [2], and with adult wheeze [5]. In a recent report in the European Respiratory Journal, VAN DER GUGTEN et al [6] showed that rapid infantile growth velocity is a risk factor for asthma/decreased lung function, up to the age of 5 years. This evidence is in keeping with our own findings of a positive association of rapid infantile growth velocity with ever wheeze and asthma incidence in preschool children.…”
mentioning
confidence: 99%
“…On this basis, we hypothesised that differential growth velocity, within the first 6 months of life, could be diversely linked to paediatric wheezing illnesses. Establishing such an interaction still eludes us, due to limited and conflicting evidence [1][2][3][4][5][6] and age-specific differences in bronchial function/structure [3]. We, therefore, opted to investigate a potential correlation in two populations of children of different ages, the Growth, Exercise and Nutrition Epidemiological Study In preSchoolers (GENESIS) study and the Healthy Growth Study cohorts (preschool and late childhood, respectively); thereby, we also appraised any age-definable discrepancies.…”
mentioning
confidence: 99%